Discourse as Social Practice on Abdul Qodir Jaelani (AQJ) Case - Syukri, Suhartini; Humaerah, Isna (LPPM Universitas Mercu Buana Yogyakarta, 2015)
This study aims at describing social practices and explaining social agents’thought and belief in the discourse of Abdul QodirJaelani (AQJ). It uses a descriptivequalitative approach in the form of discourse analysis, by utilizing the CriticalDiscourse Analysis (CDA) and appraisal devices as instruments. The data obtainedwere 10 written newspaper textsof AQJ case taken from the Jakarta Post onlinenewspaper. The units of analyses of the study are the whole texts in general and theclauses in particular. The results show that in situational level, the news productionsare based on the continuity of situational development of AQJ case; in institutionallevel, the economic media of the Jakarta Post is more stable and the politics mediainvolves the journalists’ ideology stance in which represent readers’ ideology; in thesocial level, the news attempt to attract readers’ critical thinking of the AQJ case.Moreover, the social agents employed all three resources of attitudes that tend to benegative in terms of judgment, appreciation and affect. In sum, this study shows thatmeanings were realized through the representation of social agents and social events,afterwards the evaluation of kinds of attitudes were also negotiated in the news texts ofAQJ.Keywords : appraisal system, discourse analysis, news articles, social agents, socialpractice